Inwestycja w wykształcenie - doświadczenia bydgoskich studentów (Kronika Bydgoska, 2012)
Education, development of competence can be treated as an investment - as referred to by the aspect of the theory of human Capital contained in the slogan ‘Man - the best investment’. Shortages of detailed data on the ratę of return of this investment do not allow direct assessment whether studying is really investing, hence with the use of existing data and own research an attempt to assess the investment importance of studying was madę. The analysis covers information on the fate of graduates in the scope of: time and paths of finding jobs, conformity of first job and education profile, and participation in continuous education.